2003
DOI: 10.1152/ajpregu.00476.2002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ANG II type 1 and 2 receptors on oxidative stress, renal NADPH oxidase, and SOD expression

Abstract: Oxidative stress accompanies angiotensin (ANG) II infusion, but the role of ANG type 1 vs. type 2 receptors (AT 1-R and AT2-R, respectively) is unknown. We infused ANG II subcutaneously in rats for 1 wk. Excretion of 8-isoprostaglandin F 2␣ (8-Iso) and malonyldialdehyde (MDA) were related to renal cortical mRNA abundance for subunits of NADPH oxidase and superoxide dismutases (SODs) using real-time PCR. Subsets of ANG II-infused rats were given the AT 1-R antagonist candesartan cilexetil (Cand) or the AT 2-R a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
289
2
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 292 publications
(309 citation statements)
references
References 50 publications
17
289
2
1
Order By: Relevance
“…Previously, we found that the normal kidney expressed the mRNA and protein for all of the subunits for phagocyte NAD(P)H oxidase and the mRNA for Nox-1 and Nox-4 (14) and for EC-, IC-, and Mn-SOD (19). Prolonged infusion of Ang II activates NAD(P)H oxidase in blood vessels (1,2,10,12), where it increases expression of the p22 phox , Nox-1, and Nox-4 components in VSMC from conduit vessels (33-35) and p67 phox in vascular adventitial cells (36).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Previously, we found that the normal kidney expressed the mRNA and protein for all of the subunits for phagocyte NAD(P)H oxidase and the mRNA for Nox-1 and Nox-4 (14) and for EC-, IC-, and Mn-SOD (19). Prolonged infusion of Ang II activates NAD(P)H oxidase in blood vessels (1,2,10,12), where it increases expression of the p22 phox , Nox-1, and Nox-4 components in VSMC from conduit vessels (33-35) and p67 phox in vascular adventitial cells (36).…”
Section: Discussionmentioning
confidence: 96%
“…RNA isolation and RT were performed using oligonucleotide and methods described previously (14,19). Briefly, total RNA was isolated from the kidney cortex with guanidinium isothiocyanate (Qiagen, Valencia, CA) and treated with DNase.…”
Section: Mrna Isolation and Real-time Quantitative Rt-pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…The primers were all obtained from previous published sequences and were ordered through Geneworks (Australia): NOX2 [37], p22 phox [35], CuZn-SOD, MnSOD and Ec-SOD [36]. …”
Section: Methodsmentioning
confidence: 99%
“…In kidney, Nox-dependent ROS is produced in response to agonists that bind to D1-like receptors [103], to Angiotensin II [104,105] and to H + fluxes [106]. Although physiological roles are not well understood, Nox enzymes have been suggested to function in normal renal physiology in secretion of erythropoietin [100], in renal regulation of blood pressure [103], regulation of mesangial cell protein synthesis [107] and in innate immunity [23].…”
Section: Nox Enzymes Ros and Renal Disease A Renal Nox Enzymesmentioning
confidence: 99%